2021
DOI: 10.5582/ddt.2021.01302
|View full text |Cite
|
Sign up to set email alerts
|

Drug discovery to treat COVID-19 two years after its outbreak

Abstract: vaccine, drug, pandemic Coronavirus disease 2019 (COVID-19) has had a significant impact on human health and economic development over the past two years. Therapeutics in combination with vaccines are critical measures to fight the pandemic. The three areas of drug development are blocking the entry of SARS-CoV-2 into cells, suppressing viral replication inside cells, and regulating the immune system, and important advances have recently been made in those areas. Increasing numbers of neutralizing antibodie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…There is an ongoing search for antiviral drugs against SARS-CoV-2 that can complement the currently available monoclonal antibody preparations and the three approved small-molecule drugs remdesivir, molnupiravir, and nirmatrelvir [Gao & Sun, 2021]. Effective antiviral drugs and drug combinations will be particularly important for immunocompromised individuals, who cannot effectively be protected by vaccination [Gentile & Schiano Moriello, 2022].…”
Section: Introductionmentioning
confidence: 99%
“…There is an ongoing search for antiviral drugs against SARS-CoV-2 that can complement the currently available monoclonal antibody preparations and the three approved small-molecule drugs remdesivir, molnupiravir, and nirmatrelvir [Gao & Sun, 2021]. Effective antiviral drugs and drug combinations will be particularly important for immunocompromised individuals, who cannot effectively be protected by vaccination [Gentile & Schiano Moriello, 2022].…”
Section: Introductionmentioning
confidence: 99%
“…These results showed that among all the compounds, compound 4 exhibits reasonably good binding energies for both proteins of SARS‐CoV‐2, which are docked to the catalytic sites of M PRO and spike proteins. Additionally, we have performed docking studies for two positive control compounds including Remdesivir and Nirmatrelvir which are well‐known COVID‐19 drug compounds [37] . Nirmatrelvir is very recently approved oral drug as developed by Pfizer, which also an M pro enzyme inhibitor [38] .…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, we have performed docking studies for two positive control compounds including Remdesivir and Nirmatrelvir which are well-known COVID-19 drug compounds. [37] Nirmatrelvir is very recently approved oral drug as developed by Pfizer, which also an M pro enzyme inhibitor. [38] For comparative purpose, we have performed docking of Remdesivir and Nirmatrelvir under the similar calculation conditions.…”
Section: Computational Study Binding Energy and Inhibition Constants ...mentioning
confidence: 99%
“…Considering the limited approved drugs and the withdrawal of Remdesivir from clinical use for COVID-19, there is an essential need for targeted therapeutics and effective treatment options [ 7 , 8 ]. To address this issue, this study endeavours to utilise molecular docking based virtual screening tool to identify flavonoid hits as prospective anti-COVID-19 agents.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%